Trading behavior in S&P 500 index futures - Smales, Lee (2016)
This article examines the determinants of trading decisions and the performance of trader types, in the context of the E-Mini S&P 500 futures and S&P 500 futures markets. Speculators and small traders tend to follow positive feedback strategies while hedgers dynamically adjust positions in response to market returns. Such strategies apparently reverse during the 2008-09 financial crisis. Investor sentiment and market volatility play an important role in determining the net trading position of traders across the sample period. While all trader types are better at foreseeing market upturns, an out-of-sample test suggests that speculators and small traders have some predictive ability for short-term market returns.